2017
DOI: 10.3892/etm.2017.4959
|View full text |Cite
|
Sign up to set email alerts
|

Oral colon-specific drug delivery system reduces the nephrotoxicity of rhubarb anthraquinones when they produce purgative efficacy

Abstract: Rhubarb is commonly used to treat constipation in China and anthraquinones (AQs) are the active components present in rhubarb. However, an increasing number of studies have reported that AQs induce nephrotoxicity. In the present study, rhubarb total free anthraquinones (RTFA) oral colon-specific drug delivery granules (RTFA-OCDD-GN) were prepared to determine whether RTFA-OCDD-GN could reduce the nephrotoxicity that occurs when AQs produce purgative efficacy. RTFA-OCDD-GN were prepared using pH-enzyme double-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Metabolomics is a discipline that has grown up after proteomics and genomics. 11 , 12 The metabolic network of biological systems can be derived by observing the dynamic changes in metabolites before and after stimulation or perturbation of organism systems on the basis of various analytical tools. 13 , 14 Metabolomics is widely used in various scientific fields due to its high pathway integrity, high sensitivity, and high selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics is a discipline that has grown up after proteomics and genomics. 11 , 12 The metabolic network of biological systems can be derived by observing the dynamic changes in metabolites before and after stimulation or perturbation of organism systems on the basis of various analytical tools. 13 , 14 Metabolomics is widely used in various scientific fields due to its high pathway integrity, high sensitivity, and high selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…It contains Anthraquinones (AQs) in Rheum australe . An increasing number of studies have reported that AQs induce nephrotoxicity [ 66 ]. The young leaves of Phytolacca acinosa are used as wild vegetables, but the red roots of it are poisonous and inedible [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the β-type glycoside bonds in conjugates prevents their hydrolysis by α-glucosidase in the upper gastrointestinal tract and, as a consequence, they are hydrolysed to free anthraquinones by bacterial β-glucosidases in the colon. Recently, a Chinese research group designed oral colon-specific drug delivery granules, containing the total free anthraquinones to improve their purgative effect and to reduce anthraquinone nephrotoxicity [ 131 , 132 ]. The postprandial hyperlipidemia-lowering effect and improvement in gastrointestinal transit in diabetic rats was reported for aqueous extract from the rhizome of R. palmatum , administered at doses of 150 and 300 mg/kg b.w.…”
Section: Molecular Targets For Rhubarb-derived Substancesmentioning
confidence: 99%